The Role of Accounting in Family Financial Management Strategies in the COVID-19 Era: Peran Akuntansi Dalam Strategi Pengelolaan Keuangan Keluarga pada Era COVID-19 - Evelina, Aisyah Quinta; Abidin, Fityan Izza Noor (Indonesian Journal of Law and Economics Review, 2022)
This study aims to find out how the role of accounting in family financial management strategies in the COVID-19 era. This research is a type of qualitative descriptive research using interpretive studies in order to get maximum results. Using research with primary data results which include in-depth interviews with the relevant resource persons in this case are housewives whose family income has been affected by COVID-19 by documenting it in written form, photos and then the data will be processed into main data. The results of the research that have been carried out, the conclusion that can be drawn is that accounting in financial management is not always in line with existing theories. Lack of understanding about recording or accounting in the household is a major problem, so there are still many difficulties in managing finances. Especially with the COVID-19 pandemic. Changes in the amount of income require the management of family finances to make a priority scale. In various aspects that become the formulation of the research problem, it is known that good financial management records do not provide significant difficulties for financial management in the future.